Research Impact of Shorting Mechanism on Firms’ Innovation Quality: Based on Listed Companies’ Perspective - Pan, Qi (International Journal of Global Economics and Management, 2024)
The application of a shorting mechanism can make investors pay more attention to the negative information of firms and thus have an impact on managers’ innovation decisions. This paper uses the implementation of China’s securities financing policy as a quasi-natural experiment to explore the impact of the policy on the quality of corporate innovation. According to the data of A-share listed companies from 2007 to 2022, a double-difference model is used to assess the impact of the implementation of the short-selling mechanism on the quality of corporate innovation. The study shows that the policy significantly promotes the improvement of corporate innovation quality. Meanwhile, the incentivizing effect of the shorting mechanism on enterprise innovation quality is more significant in non-state-owned companies. The findings of the study provide important policy insights for the implementation of the innovation-driven development station strategy in China.